Exploring how to enhance SMES practices in the tourism sector in terms of service quality and sustainability - Loureiro, S. M. C.; Palma, P. de M.; Langaro, D. (16th Annual Conference of the EuroMed Academy of Business. Business Transformation in Uncertain Global Environments, 2023)
This study is part of RESETTING, a European program designed as a tool for "Relaunching European Smart and Sustainable Tourism Models through Digitalization and Innovative Technologies" (RESETITNG, 2022). This project aims to improve the quality of the travel experience, support the decarbonization of the tourism industry and promote more inclusive economic growth - not only for SMEs, but also for local people in the destination - by testing and integrating cutting-edge, digitally driven solutions that reduce burdensome requirements and facilitate the transition to more resilient, circular and sustainable operating models for European tourism businesses. The project will involve 60 SMEs from five countries (Portugal, Spain, Italy, Greece, and Albania). The contribution of managers with different experiences will allow them to evaluate and find solutions that can be helpful and relevant in very specific tourism contexts. This work will help to identify, propose, and validate measurement scales for a web platform developed to help SMEs evaluate their execution of different concepts. The main objective is to use a systematic literature approach to identify and analyze two core constructs: Service Quality and Sustainability. In addition, we also intend to understand how these constructs are measured in the tourism sector, especially regarding small and medium enterprises, to then propose our own measurement scales. The systematic literature review followed several criteria of quality, the scope of the study, and the use of quality ranking of journals where studies are published.